Efficacy and safety of combined intraventricular fibrinolysis with lumbar drainage for prevention of permanent shunt dependency after intracerebral hemorrhage with severe ventricular involvement: A randomized trial and individual patient data meta‐analysis. Issue 1 (24th January 2017) - Staykov, Dimitre; Kuramatsu, Joji B.; Bardutzky, Jürgen; Volbers, Bastian; Gerner, Stefan T.; Kloska, Stephan P.; Doerfler, Arnd; Schwab, Stefan; Huttner, Hagen B.
Abstract : Objective: Intraventricular hemorrhage (IVH) is a negative prognostic factor in intracerebral hemorrhage (ICH) and is associated with permanent shunt dependency in a substantial proportion of patients post‐ICH. IVH treatment by intraventricular fibrinolysis (IVF) was recently linked to reduced mortality rates in the CLEAR III study and IVF represents a safe and effective strategy to hasten clot resolution that may reduce shunt rates. Additionally, promising results from observational studies reported reductions in shunt dependency for a combined treatment approach of IVF plus lumbar drains (LDs). The present randomized, controlled trial investigated efficacy and safety of a combined strategy—IVF plus LD versus IVF alone—on shunt dependency in patients with ICH and severe IVH. Methods: This randomized, open‐label, parallel‐group study included patients aged 18 to 85 years, prehospital modified Rankin Scale ≤3, ICH volume < 60ml, Glasgow Coma Scale of <9, and severe IVH with tamponade of the third and fourth ventricles requiring placement of external ventricular drainage (EVD). Over a 3‐year recruitment period, patients were allocated to either standard treatment (control group receiving IVF consisting of 1mg of recombinant human tissue plasminogen activator every 8 hours until clot clearance of third and fourth ventricles) or a combined treatment approach of IVF and—upon clot clearance of third and fourth ventricles—subsequent placement of an LD for drainage of cerebrospinal fluid (CSF; intervention group). The primary endpoint consisted of permanent shunt placement indicated after a total of three unsuccessful EVD clamping attempts or need for CSF drainage longer than 14 days in both groups. Secondary endpoints included IVF‐ and LD‐related safety, such as bleeding or infections, and functional outcome at 90 and 180 days. Conducted endpoint analyses used individual patient data meta‐analyses. The study was registered atclinicaltrials.gov (NCT01041950). Results: The trial was stopped upon predefined interim analysis after 30 patients because of significant efficacy of tested intervention. The primary endpoint was analyzed without dropouts and was reached in 43% (7 of 16) of the control group versus 0% (0 of 14) of the intervention group ( p = 0.007). Meta‐analyses were based on overall 97 patients, 45 patients receiving IVF plus LD versus 42 with IVF only. Meta‐analyses on shunt dependency showed an absolute risk reduction of 24% for the intervention (LD, 2.2% [1 of 45] vs no‐LD, 26.2% [11 of 42]; odds ratio [OR] = 0.062; confidence interval [CI], 0.011–0.361; p = 0.002). Secondary endpoints did not show significant differences for CSF infections (OR = 0.869;CI, 0.445–1.695; p = 0.680) and functional outcome at 90 days (OR = 0.478; CI, 0.190–1.201; p = 0.116), yet bleeding complications were significantly reduced in favor of the intervention (OR = 0.401; CI, 0.302–0.532; p < 0.001). Interpretation: The present trial and individual patient data meta‐analyses provide evidence that, in patients with severe IVH, as compared to IVF alone, a combined approach of IVF plus LD treatment is feasible and safe and significantly reduces rates of permanent shunt dependency for aresorptive hydrocephalus post‐ICH. ANN NEUROL 2017;81:93–103